Development of a software system for optical tweezers - Chia, Yong Jie (2014)
Optical tweezers (OT) have demonstrated its capabilities in manipulating cells and performing sophisticated experiments under the spectroscopy, nanotechnology and biophysics fields. The key function of OT is to manipulate cells with non-contact force through the optical trapping created by the laser beam. Some of its applications include transporting cells to a desired position and organizing cells in a unique manner. LabView, the main graphical user interface in this project will be used to carry out optical trapping for both single and multiple cells manipulation. An implementation of a feedback control loop to realize automated trapping of cells will also be presented with distinct readings such as the size and velocity of cells for future expansion in the project. Most importantly, with regards to the worldwide ageing population issue, trends of employing OT in the tissue engineering and regenerative medicine can also be look into. Lastly, recommendations for future work of OT are also highlighted in this report.